Non-Homothetic Growth Models for the Environmental Kuznets Curve - Katsuyuki Shibayama; Iain Fraser (University of Kent, School of Economics, 2012)
In this paper, we study the impact of the economic growth on the environment. First, we show that, at each income level, eta determines the direction of environmental degradation, where eta is the elasticity of substitution between consumption and the environment. That is, for eta large enough, as income increases people accept environmental degradation by enjoying more consumption as compensation, and vice versa. Intuitively, there are two effects operating; the income effect encourages the demand for better environmental quality simply because the environment is a normal good, whereas the substitution effect discourages it because maintaining the environment becomes more expensive as technology improvement increases the production of the general consumption good per unit of emission. The strength of the substitution effect is governed by eta. Hence, the impact of economic growth on the environment crucially depends on eta. Second, we demonstrate that exponential utility generates the environmental Kuznets curve (EKC) under a wide class of models without adding any other peculiar assumptions. Under exponential utility, eta is decreasing in income; intuitively, when a country is poor (large eta), people seek more consumption at the cost of environmental degradation, but, once it becomes rich enough (small eta), they seek increased environmental quality.
Keywords: O13; Q56; 330; Environmental Kuznets Curve; Economic Growth; Non-Homothetic Preferences; Generalized Isoelastic Preferences